Experiential Learning to Cultivate Medical Students' Scientific Research Skills - Yuan, Yan; Angsuwotai, Nadda (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2026)
This study explores experiential learning in self-directed learning, students' innovative abilities, teaching methodology, practical activities, and the scientific research skills of medical students, and analyzes the significant influence of experiential learning on these skills. The sample group consists of 425 students selected by purposive sampling from second- and third-year medical majors at Kunming Health Vocational College. The questionnaire was distributed to students, who generated a QR code and survey link on the Wenjuanxing platform and shared them with participants through institutional communication channels. The data analysis included mean and standard deviation, t-tests, one-way ANOVA, and multiple linear regression. The results of the study showed that (1) The average mean of experiential learning is at a high level. (2) The significant influence of experiential learning is only 2 variables, these are self-directed learning (SDL) and students' innovative abilities (SIA), toward the medical students' scientific research skills (SRA) at the 0.01 level. The scientific research skills of medical students are essential to promote medical progress and innovation in clinical practice.